2014
DOI: 10.1089/met.2014.0018
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cystatin C with Measures of Obesity and Its Impact on Cardiovascular Events Among Healthy US Adults

Abstract: CysC correlated better with measures of visceral adiposity (WC and WHR) compared to BMI and appears to be a better predictor of adverse cardiovascular outcomes among those with anthropometric measures not suggestive of obesity compared to those with abnormal measures of anthropometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Another study illustrated a stronger correlation between CysC and WC compared to BMI. [40] These data indicate that the close association between CysC and MetS may be mediated by visceral fat.…”
Section: Discussionmentioning
confidence: 91%
“…Another study illustrated a stronger correlation between CysC and WC compared to BMI. [40] These data indicate that the close association between CysC and MetS may be mediated by visceral fat.…”
Section: Discussionmentioning
confidence: 91%
“…35 Magnusson 2013 et al, showed that abdominal obesity is significantly associated with increased baseline levels of Cystatin C. Another study illustrated a stronger correlation between Cystatin C and WC compared to BMI. 36,37 Moreover, cystatin C was well expressed in human adipose tissue, subcutaneous and omental fat, says that cystatin C may has a role in inflammation and controlling adipose tissue mass by inhibiting cathepsins. Hence serum Cystatin C causes stability of plaques which benefits the individuals with normal kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent trial Panaich et al have tried to explore the link between cystatin C and anthropometric measures and its influence on cardiovascular mortality, and they found that cystatin C corelated better with measures of visceral adiposity that included waist circumference and waist to hip ratio compared to BMI. It appeared to predict cardiovascular outcomes better in those with measures that do not suggest obesity than those who have abnormal anthropometric measures [55].…”
Section: Cystatin C As a Predictor Of Cv Disease In Diabetes Mellitusmentioning
confidence: 96%